kinerja pegawai kantor desa dalam memberikan pelayanan administrasi kepada msyarakat di desa purwosuman kecamatan sidoharjo kabupaten sragen: performance of village office employees in providing administrative services to communities in purwosuman village. sidoharjo district sragen district - Septiana, Klariza; Haryanto, Aris Tri; Winduro, Wirid (Solidaritas, 2023)
The performance of village office employees is one of the determining factors in efforts to improve the quality of service to the community. This study aims to determine the performance of Village office employees in providing administrative services to the community in Purwosuman Village, Sidoharjo District, Sragen Regency. This study uses six performance indicators according to Robbins' 2006 theory which consist of: (1) quality, (2) quantity, (3) timeliness, (4) effectiveness, (5) independence, (6) work commitment. The method used is qualitative and the data analysis technique used is descriptive. A qualitative approach with descriptive data analysis using the Miles, Huberman, and Saldana models, namely by (1) Data Collection, (2) Data Condensation, (3) Data Presentation, and (4) Drawing Conclusions and using observation, interview, and Documentation methods . The results showed that the performance of village office employees in providing administrative services to the community in Purwosuman Village, Sragen Regency was still not fully in accordance with community expectations, the quality of work of employees in providing information, the quantity of work of employees in making data, timeliness according to SOP, employee effectiveness in the use of assistive devices, the independence of employees in carrying out their duties, and the work commitment of employees in being accountable for their duties. To improve the quality of good employee performance there are several improvements in timeliness, responsiveness and means to produce higher quality employee performance. Keywords: Employee Performance, Administrative Services, quality, quantity, timeliness, effectiveness. Independence, work commitment.